Short communication. Post-thawing evaluation of Spanish ibex (Capra pyrenaica hispanica) epididymal spermatozoa recovered postmortem - Santiago-Moreno, J.=700 1 Toledano-Diaz, A.; Pulido-Pastor, A.; Gomez-Brunet, A.; Gonzalez-Bulnes, A.; Lopez-Sebastian, A.
(Es, En)
ilus., 11 ref.
Keywords: CAPRINOS; SEMEN; TESTICULOS; CONGELACION; CONSERVACION DEL SEMEN; CONSERVACION BIOLOGICA; ESPAÑA